2011
DOI: 10.1111/j.1360-0443.2011.03499.x
|View full text |Cite
|
Sign up to set email alerts
|

Vested interests in addiction research and policy. Alcohol industry use of social aspect public relations organizations against preventative health measures

Abstract: Drinkwise has been used by the alcohol industry to create an impression of social responsibility while promoting interventions that maintain profits and campaigning against effective interventions such as higher taxes on alcohol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
92
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(94 citation statements)
references
References 22 publications
0
92
0
Order By: Relevance
“…Although alcohol industry groups publicly state their commitment to reducing underage drinking, 28 researchers and health experts have expressed concern about the industry's apparent conflicts of interest and questioned the effectiveness of industry-led initiatives that purport to address harm associated with alcohol. 29 For example, a study by Pettigrew et al identified that a youth-targeted 'responsible drinking' campaign developed by an alcohol industry social aspects/public relations organisation may be counterproductive. 30 Furthermore, previous studies have shown that alcohol consumption is associated with large economic costs.…”
Section: Discussionmentioning
confidence: 99%
“…Although alcohol industry groups publicly state their commitment to reducing underage drinking, 28 researchers and health experts have expressed concern about the industry's apparent conflicts of interest and questioned the effectiveness of industry-led initiatives that purport to address harm associated with alcohol. 29 For example, a study by Pettigrew et al identified that a youth-targeted 'responsible drinking' campaign developed by an alcohol industry social aspects/public relations organisation may be counterproductive. 30 Furthermore, previous studies have shown that alcohol consumption is associated with large economic costs.…”
Section: Discussionmentioning
confidence: 99%
“…In affording respect to each of these realms, researchers honor what Kass (2002) describes as "the rich broth of our social, civil, cultural, and spiritual life together and of the ways in which it seasons us without our knowledge" (p. 65). The well-being of the individual, of institutions, and of society as a whole is at stake in assessing the ethical issues that arise in addiction research, as illustrated by recent studies of corporate social responsibility programs, research on chronic drug users, and the use of animals involved in addiction research (Casswell, 2013;Fisher, 2011;Lynch et al, 2010;Miller et al, 2011). Consider the following scenario as an invitation to apply our discussion up to this point to the realities of a possible research publication situation:…”
Section: The Ethical Challengementioning
confidence: 99%
“…Commercial sector funding can alter research priorities by shaping the research agenda through funding provision or by lobbying decision-makers or fundersfor example, by privileging intervention approaches that are less likely to be effective. 407,408 The sector's involvement in the design or conduct of research has sometimes been found to result in more biased research. 409,410 The dissemination process could also be affected, with greater risks of non-publication and misrepresentation of research findings.…”
Section: Engaging With the Commercial Sectormentioning
confidence: 99%